HUBUNGAN PENGETAHUAN DAN SIKAP IBU USIA SUBUR DENGAN PEMERIKSAAN IVA DI PUSKESMAS SUNGAI LIMAU - Nurhayati Nurhayati (Jurnal Akademika Baiturrahim Jambi, 2019)
Cervical cancer is the second most common type of cancer in women and is the biggest cause of death in the world. The incidence of cervical cancer in Indonesia is <19.92% per 100,000 women per year. Prevention of cervical cancer can be done by early detection of IVA examination. The UPTD of the Gasan Gadang Community Health Center is the lowest achievement of the IVA examination of 2,322 WUS in which only 45 people conducted IVA examinations. The purpose of this study was to determine the relationship between the level of knowledge and attitudes of Fertile Age Mothers Against IVA Examination. This type of research is descriptive analytic with a cross sectional study design. The population in this study was 127 people and a sample of 56 people was taken by simple random sampling. The dependent variable is IVA examination while the independent variable is the level of knowledge and attitude. Data was collected through questionnaires given to women of childbearing age based on inclusion criteria. Data analysis was done by univariate (frequency distribution) and bivariate by chi square test (p = 0.05). The results showed that more than half of the respondents had a low level of knowledge, more than half of the respondents were negative about IVA examination, and most respondents did not conduct IVA examinations. The results of bivariate analysis have a relationship between the level of knowledge (p = 0.001) and attitude (p = 0.018) with IVA examination. It can be concluded that a significant relationship between the level of knowledge and attitudes toward IVA examination. Suggestions for research sites, namely Sungai Limau Health Center to further improve counseling and a good approach must be made to the community, especially mothers of childbearing age, to IVA examination.